2016
DOI: 10.1515/jvetres-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of different strains of Babesia canis in dogs in eastern Poland

Abstract: Introduction: The aim of this study was to carry out a genetic analysis of Babesia canis isolates detected in dogs in eastern Poland and to study the correlation of the protozoa variant with a specific geographical region. Material and Methods: PCR was used to identify strains of B. canis from naturally infected animals (240 dogs from four provinces: Mazowieckie, Lublin, Podlasie, and Podkarpacie) by amplifying and sequencing a fragment of the 18S rRNA gene. Results: Sequencing the PCR products led to the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Thus, when comparing their Slovenian samples to the reference AY072926, Duh et al [ 30 ] found three genotypes differing at two consecutive positions, 609 and 610 (GA/AG/AA), of the complete gene [ 29 , 30 ]. Since then, other molecular surveys have reported on this single-nucleotide polymorphism as an intra-specific genetic variation of B. canis isolates from different European countries, such as Poland [ 33 , 47 ], Croatia [ 34 ], Switzerland [ 48 ], Lithuania [ 39 , 49 ], Latvia [ 41 ], and Russia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, when comparing their Slovenian samples to the reference AY072926, Duh et al [ 30 ] found three genotypes differing at two consecutive positions, 609 and 610 (GA/AG/AA), of the complete gene [ 29 , 30 ]. Since then, other molecular surveys have reported on this single-nucleotide polymorphism as an intra-specific genetic variation of B. canis isolates from different European countries, such as Poland [ 33 , 47 ], Croatia [ 34 ], Switzerland [ 48 ], Lithuania [ 39 , 49 ], Latvia [ 41 ], and Russia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GA variant, displaying guanine and adenine at the aforementioned positions, was found in our study as a single infection in only two samples (9.1%). This genetic variant was detected for the first time in Romanian dogs but is considered common in other European countries where it is found most often, such as Croatia, at 58.1% (57/98 isolates); Poland, at 44.6% (107/240 isolates); and Lithuania, at 34.2% (13/38 isolates) [ 34 , 39 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, the number of canine babesiosis incidents in Poland and in other Central European countries has increased [6,7,12,14]. This situation is probably a result of the rapid development of tourism with companion animals, such as domestic dogs and cats, and the wider spreading of ticks and B. canis vectors to new locations [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Babesiosis is a tick-transmitted disease caused by piroplasms of the genus Babesia and characterized by haemolytic anaemia and fever, with occasional haemoglobinuria and death (Zygner et al 2013). Ticks may be able to transmit a number of piroplasms species to cattle (B. bigemina, B. bovis), horses (B. caballi, Thieleria equi), cats (B. cati, B. felis), dogs (B. canis, B. gibsoni, B. rossi, B. vogeli, and B. vulpes), and humans (B. divergens, B. durcani, B. microti, and B. venatorum) (Adaszek and Winiarczyk 2008, Adaszek et al 2009, Łyp et al 2016. In Europe two large canine Babesia species (B. canis and B. vogeli) are the most frequently detected piroplasms in domestic dogs.…”
Section: Introductionmentioning
confidence: 99%